2004
DOI: 10.1016/j.nucmedbio.2004.05.001
|View full text |Cite
|
Sign up to set email alerts
|

227Th-EDTMP: A potential therapeutic agent for bone metastasis

Abstract: The biodistribution of 227 Th-EDTMP and retention of its daughter nuclide 223 Ra were examined. 227 Th-EDTMP was found to show high uptake and long-term retention in bone. The clearance of 227 Th-EDTMP from blood and soft tissues was rapid and the femur-to-tissue uptake ratios reached more than 100 within 30 min for all tissues except the kidney. Seven and 14 days after injection of 227 Th-EDTMP, the retention index of 223 Ra in bone showed high values, and the differences between these time points were not si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 20 publications
0
15
0
4
Order By: Relevance
“…Several studies have shown the successful use of alpha particle-emitting nuclides, such as 211 At, 213 Bi and 227 Th for radionuclide therapy due to their higher liner energy transfer and shorter path length as compared to beta particle-emitting nuclides. [19][20][21] However, one possible issue is the control of the radiation to normal tissues (kidney or bone marrow etc.) due to its high cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the successful use of alpha particle-emitting nuclides, such as 211 At, 213 Bi and 227 Th for radionuclide therapy due to their higher liner energy transfer and shorter path length as compared to beta particle-emitting nuclides. [19][20][21] However, one possible issue is the control of the radiation to normal tissues (kidney or bone marrow etc.) due to its high cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…EDTMP has an affinity for the hydroxyapatite in bone matrix, resulting in high uptake and long-term retention of the 153 Sm in bone (27). A review of recent published series (28) demonstrated pain relief with response rates of 40-95%.…”
Section: Discussionmentioning
confidence: 99%
“…Emission of g-photons allows for scintigraphic imaging of both isotopes. Biodistribution of 227 Th-citrate indicates high uptake in the femur and parietal bone (25). 223 Ra is an alkaline earth metal similar to calcium that, like 227 Th, preferentially accumulates in sites of bone mineralization, binding into hydroxyapatite.…”
Section: Atmentioning
confidence: 99%
“…223 Ra is an alkaline earth metal similar to calcium that, like 227 Th, preferentially accumulates in sites of bone mineralization, binding into hydroxyapatite. g-ray spectroscopy of the femur showed that, if released, 223 Ra redistributes to the bone because of the a-recoil energy, resulting in an increased dose to the bone surface (25). The lack of suitable chelating agents to coordinate 223 Ra limits the development of radioconjugates.…”
Section: Atmentioning
confidence: 99%